A Review of techniques for Automatic detection and diagnose of mango pathologies (International Journal of Engineering and Computer Science, 2017)
The agriculture is the sole area that serves the entire life on earth. With aid of advanced technology research with new challenges in the field of agriculture is increase the production and profit. The different diseases and symptoms on any part of plant cause significant loss in production and economy to farmers as well as country. Thus the techniques for automatic disease detection and diagnose of agriculture crop or plant plays a major in disease management.  This paper presents a review on methods that use digital image processing techniques to detect, recognize and classify plant diseases from digital image and concludes with discussion of more useful problems in the domain and future direction.